Social and economic actors in the evaluation of translation technologies. Creating meaning and value when designing, developing and using translation technologies - Mihalache, Iulia (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Evaluation of translation technologies is a social activity, which involves the establishment of knowledge communities as well as the creation of competition to produce better tools. Companies developing translation technologies need to encourage the evaluation of their tools (through online forums, discussion lists, blogs, product communities, community translation, etc.), since evaluating the technology implies spreading and sharing knowledge about it; and sharing the same knowledge or the same modes of thinking and operation, rather than sharing the same material resources, represents the basis of future economic competition. When exchanging knowledge about technologies, translators engage in social activity: they express their opinions and feelings about the technologies they are using, they make judgments about the worth or value of a specific technology, they influence others’ decisions or they believe their thoughts will have an impact on decisions companies will make. This article investigates the use of translation technology evaluation criteria as they are represented in several translators’ communities and it calls for a multidisciplinary approach when analysing translation technologies adoption, use and evaluation.